Skeletal muscle fiber plasticity: Heat shock proteins and satellite cell activation - Yasuharu Oishi; Tomonori Ogata (Japanese Society of Physical Fitness and Sports Medicine, 2012)
Skeletal muscles have defensive and regenerative systems to protect them from severe injury and/or fiber degeneration. Several stresses, including muscle-contraction during exercise and heat stress, induce the specific proteins named heat shock proteins (HSPs) or stress proteins. Many studies have shown that HSPs protect muscle from injury or stimulate repair of injured muscles. Injured or degenerated skeletal muscle fibers have the potential to recover to normal size and function. This regenerative ability of muscle fibers largely depends on a specific cell known as the satellite cell, which is located between the basal lamina and plasma membrane of the muscle fibers. Satellite cells are well known as muscle-specific stem cells and play crucial roles in muscle hypertrophy and fiber regeneration by activation, proliferation, differentiation, and fusion to the existing fibers, or by forming new myotubes in new growing fibers. This review focuses on the functional roles of heat shock proteins and also on the fiber regeneration process with activation of satellite cells in skeletal muscles.